Good corporate governance. Pada badan usaha manufaktur, perbankan, dan jasa keuangan lainnya - ZARKASYI, Moh. Wahyudi (Alfabeta, 2008)
Good corporate governance. Pada badan usaha manufaktur, perbankan, dan jasa ...